Dampak Good Government Governance terhadap Kinerja Value For Money Method pada Satuan Kerja -Perangkat Daerah - Jatmiko, Bambang; Damayanti, Eliza (E-Jurnal Akuntansi, 2020)
This study aims to test dan empirically prove the impact of Good Government Governance which consists of Transparency, Accountability, dan Legal Rules on the Performance of  Value for Money on Regional Work Units (SKPD) in Kebumen Regency. The research method in this study uses a purposive sampling technique that is the technique of determining the sample with certain considerations. The population in this study is the Secretary, Head of Subdivision, Head of Division, dan Head of Section at SKPD Kebumen Regency. In this study a sample of 91 respondents. The analytical tool used in this study is multiple linear regression using SPSS version 15 for Windows. The test results show that partially transparency dan legal rules have a significant positive effect on economics, efficiency, dan effectiveness, while accountability does not have a significant effect on economics, efficiency, dan effectiveness . Keywords: Good Government Governance; Value for Money.